Mechanism of Photodynamic Inactivation and Its Advantages and Disadvantages in Food Applications - Yuanyuan MENG; Haiquan LIU; Yingjie PAN; Yong ZHAO (Shipin gongye ke-ji, 2022)
Hazardous microorganisms are an important factor for causing food quality and safety problems. Antibiotics effectively inhibit bacteria, and the resistance of microorganisms prevents them from being effectively controlled, which not only aggravate the food safety risks, but also cause serious economic losses. Hence, there is an urgent need to develop other alternative sterilization technologies. Photodynamic inactivation uses light to stimulate photosensitizer, which can produce reactive oxygen species. The morphological structure, cell membrane, nucleic acid and protein of pathogenic bacteria are destroyed by reactive oxygen species, leading to the death of bacteria. This mechanism triggers a variety of death mechanisms that bacteria are difficult to develop tolerance. Photodynamic inactivation achieves a good bactericidal effect. However, this sterilization technology pays less attention to the influence of food ingredients and quality, which limits its promotion and application in the food field. This review summarizes the mechanism and influencing factors of photodynamic inactivation. The application and research progress of photodynamic inactivation in the food industry are introduced, and new insights on the advantages and disadvantages of photodynamic inactivation in food applications are put forward, which aims to provide reference for the application of photodynamic inactivation in food industrial.